2021
DOI: 10.3390/ijgi10020103
|View full text |Cite
|
Sign up to set email alerts
|

Escaping from Cities during the COVID-19 Crisis: Using Mobile Phone Data to Trace Mobility in Finland

Abstract: The coronavirus disease 2019 (COVID-19) crisis resulted in unprecedented changes in the spatial mobility of people across societies due to the restrictions imposed. This also resulted in unexpected mobility and population dynamics that created a challenge for crisis preparedness, including the mobility from cities during the crisis due to the underlying phenomenon of multi-local living. People changing their residences can spread the virus between regions and create situations in which health and emergency ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(39 citation statements)
references
References 46 publications
1
38
0
Order By: Relevance
“…In the beginning of June (week 23), restrictions on social gatherings were partially loosened to allow larger gatherings of 10-50 people in public spaces (e.g., restaurants and sport events). The rate of weekly detections steadily decreased to less than 100 during this time, and the number of tests per week also dropped to half during summer until week 26 (end of June) 14 . International travel restrictions were lifted between European countries with low infection rates (less than 25 per 100,000) 15 on July 8, 2020 (week 28).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…In the beginning of June (week 23), restrictions on social gatherings were partially loosened to allow larger gatherings of 10-50 people in public spaces (e.g., restaurants and sport events). The rate of weekly detections steadily decreased to less than 100 during this time, and the number of tests per week also dropped to half during summer until week 26 (end of June) 14 . International travel restrictions were lifted between European countries with low infection rates (less than 25 per 100,000) 15 on July 8, 2020 (week 28).…”
Section: Introductionmentioning
confidence: 89%
“…As part of the 43 independent introduction events, our analysis identi ed 35 introductions (81%) (95% HPD interval = [30][31][32][33][34][35][36][37][38][39]) resulting in relatively few sampled Finnish descendants (≤ 10), including 16 singleton introductions (95% HPD interval = [12][13][14][15][16][17][18][19][20]). Hence, the large majority of introductions account for a relatively small number of the lineages we sample, a pattern typically observed for all European countries (Fig.…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Willberg et al identified a significant decrease of the population presence in the largest cities of Finland after the lockdown compared to a usual week [25]. Bushman et al analyzed the compliance to social distancing in the US using mobile phone data [26].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This enabled them to keep social distancing while having an active lifestyle. A study on mobile data indicated mobility flows from urban areas to less populated rural areas, and there was a strong correlation between the increase of people and the presence of second homes [25]. Mobile work and remote services may attract more people in these areas also in the future.…”
Section: Discussionmentioning
confidence: 99%